EFEKTIVITAS TENAGA KERJA DAN INVESTASI ASING DALAM PERTUMBUHAN PDB PERKAPITA NEGARA ASEAN - Ryandhica Angga Saputra; Dwi Susilowati; Zainal Arifin (Jurnal Ilmu Ekonomi, 2021)
Increase in Gross Domestic Product (GDP) is a major problem that results in any economic development in all countries. Developing countries always have difficulty getting high economic growth, this is because developing countries have not achieved economic stability. Supporting factors, including labor and foreign investment, are factors that greatly affect the country's GDP growth. The samples of Asean countries used include Indonesia, Malaysia, the Philippines, Thailand, Myanmar, Vietnam and Cambodia with vulnerable years from 2000 to 2018. Using data on X1 Labor and X2 Foreign Investment (FDI) and processed using the panel data method on E-views and the results show that foreign labor and investment have a significant effect on GDP per capita growth in Asean countries. It is proven that the increase in foreign investment (FDI) each period will have an impact on labor demand so that the GDP per capita produced by each country will also increase.